Rapid method for quantitative analysis of the aroma impact compound, 2-acetyl-1-pyrroline, in fragrant rice using automated headspace gas chromatography - Sriseadka T. (2014)
A rapid method employing static headspace gas chromatography (HS-GC) has been developed and validated for quantitative analysis of the impact aroma compound, 2-acetyl-1-pyrroline (2AP), in grains of fragrant rice. This developed method excludes wet extraction, and the rice headspace volatiles are brought directly and automatically to GC analysis. The conditions of the static HS autosampler were optimized to achieve high recovery and sensitivity. The most effective amount of rice sample used was 1 g, which provided 51% recovery and a linear multiple headspace extraction (MHE) plot of the peak area of 2AP. The sensitivity of the method was enhanced by utilizing a megabore fused silica capillary column in conjunction with a nitrogen-phosphorus detector (NPD). Method validations performed for both static HS-GC-FID and HS-GC-NPD demonstrated linear calibration ranges of 20-10 000 (r2 = 0.9997) and 5-8000 (r2 = 0.9998) ng of 2AP/g of rice sample, respectively. The limits of detection for both systems were 20 and 5 ng of 2AP, and the limits of quantitation were 0.30 and 0.01 g of brown rice sample, respectively. Reproducibility calculated as intraday and interday coefficients of variation were 3.25% RSD (n = 15) and 3.92% RSD (n = 35), respectively, for SHS-GC-FID and 1.87% RSD (n = 15) and 2.85% RSD (n = 35), respectively, for SHS-GC-NPD. The method was found to be effective when applied to the evaluation of aroma quality, based on 2AP concentrations, of some fragrant rice samples. © 2006 American Chemical Society.